Smoking and COVID-19: A Literature Review of Cohort Studies in Non-Chinese Population Settings. (January 2021) - Rodgers, Aoife; Nadkarni, Manasi; Indreberg, Emilie Kruke; Alfallaj, Lenah; Kabir, Zubair
Background: Smoking history and its potential association with COVID-19 has attracted many researchers and the lay public alike. However, the studies published to date have several methodological limitations and are mainly from China. We set out to synthesize evidence on smoking and COVID-19 relationship drawn on cohort studies only which are published in non-Chinese population settings. Method: A systematic literature search was undertaken drawn on predefined eligibility criteria and a comprehensive search strategy following the PRISMA guideline between January 2020 and August 2020, excluding preprints and gray literature. Three specific outcomes were examined: smoking history, SARS-CoV2 infection, and COVID-19 severity. Results: Of an eligible 40 full-text studies, 7 cohort studies outside of China were finally included in this literature review through independent reviewing. Four studies were from the UK, 2 from the United States, and 1 from Turkey. The sample size ranged from 200 to more than 5000 participants. The findings broadly point to 1 direction, a higher smoking prevalence and an increased risk of smoking history on both SARS-CoV2 infection and on COVID-19 severity. Conclusion: A smoking history (either current or past) seems to negatively impact both SARS-CoV2 infection and COVID-19 severity. However, such an observation strengthens the argument to continue smoking cessation efforts both for individuals and for the general population health and well-being.